2017
DOI: 10.1002/term.2482
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel bioabsorbable implant that is substituted by adipose tissue in vivo

Abstract: Recently, adipose tissue has been regenerated by combining scaffolds, growth factors, and/or adipose-tissue-derived stromal cells. However, the safety of growth factors and adipose-tissue-derived stromal cells has not been confirmed in cancer patients. We reported the regeneration of adipose tissue in the internal space of a polypropylene mesh containing a collagen sponge (CS), without using any growth factors or cells. We herein explored the formation of adipose tissue, using the bioabsorbable implant contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 40 publications
(42 reference statements)
0
24
0
Order By: Relevance
“…22,23 It has been reported that adipose tissue can be regenerated by combining a 3D biodegradable porous scaffold with adiposederived stromal cells or bone-marrow derived mesenchymal stem cells. 24,25 A 3D scaffold for adipose tissue engineering should bear soft tissue-like mechanical properties, biocompatibility and biodegradability. 25 Gelatin has been used for the preparation of tissue regeneration scaffolds because of its high bioactivity, low antigenicity and low immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 It has been reported that adipose tissue can be regenerated by combining a 3D biodegradable porous scaffold with adiposederived stromal cells or bone-marrow derived mesenchymal stem cells. 24,25 A 3D scaffold for adipose tissue engineering should bear soft tissue-like mechanical properties, biocompatibility and biodegradability. 25 Gelatin has been used for the preparation of tissue regeneration scaffolds because of its high bioactivity, low antigenicity and low immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…In phosphate-buffered saline at 37° C,PLLA was degraded to 50% by weight within two years and PGA was completely degraded within two to three months [25]. This implant needs to be lled with the formed adipose tissue inside at least one year [12,13]. Therefore, in the next experiment, we need to investigate the regeneration of adipose tissue over a year after implantation using ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical force also affects adipogenesis, and an in vitro study reported that adipogenesis from ASCs is inhibited by mechanical compressive force [21] or mechanical stretch [22]. In our previous in vivo study, we reported the importance of maintaining the internal space for adipogenesis [12,13]. Large volumes of adipose tissue were regenerated via an autologous fat transfer using bioabsorbable, polycaprolactonebased scaffolds in a porcine model [23] and poly-4-hydroxybutyrate mesh scaffolds clinically [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations